Trait reactance as psychological motivation to reject vaccination: Two longitudinal studies and one experimental study - Soveri, Anna (Wiley, 2025)
Anti-science attitudes can be resilient to scientific evidence if they are rooted in psychological motives. One such motive is trait reactance, which refers to the need to react with opposition when one's freedom of choice has been threatened. In three studies, we investigated trait reactance as a psychological motivation to reject vaccination. In the longitudinal studies (n = 199; 293), we examined if trait reactance measured before the COVID-19 pandemic was related to people's willingness to get vaccinated against COVID-19 up to 2 years later during the pandemic. In the experimental study (n = 398), we tested whether trait reactance makes anti-vaccination attitudes more resistant to information and whether this resistance can be mitigated by framing the information to minimize the risk of triggering state reactance. The longitudinal studies showed that higher trait reactance before the COVID-19 pandemic was related to lower willingness to get vaccinated against COVID-19. Our experimental study indicated that highly reactant individuals' willingness to vaccinate was unaffected by the amount and framing of the information provided. Trait reactance has a strong and durable impact on vaccination willingness. This highlights the importance of considering the role of trait reactance in people's vaccination-related decision-making.